Pengaruh Promosi Dan Brand Image Terhadap Keputusan Pembelian Konsumen Sepatu Kolaborasi Compass Di Kebayoran Lama - Nani Sriyani (Jaanur Elbarik Indonesia, 2026)
This study aims to analyze the influence of promotion and brand image on the purchasing decision of Compass collaboration shoes in the Kebayoran Lama District, both partially and simultaneously. The method used is quantitative, with 88 respondents as the sample. The study also applies several tests, including validity test, reliability test, classical assumption test, correlation coefficient, regression, coefficient of determination, and hypothesis testing. The results show that promotion has a significant effect on purchasing decisions, with the regression equation Y = 23.303 + 0.490 X1. The tvalue is 8.072 > ttable value 1.988, and the significance value is 0.000 < 0.050, indicating that H0 is rejected and H1 is accepted. This means that promotion partially has a positive and significant effect.Brand image also has a significant influence, with the regression equation Y = 23.030 + 0.724 X2. The tvalue is 7.666 > ttable 1.988 and the significance is 0.000 < 0.050, so H0 is rejected and H2 is accepted. Simultaneously, promotion and brand image significantly influence purchasing decisions, with the multiple regression equation Y = 0.992 + 0.553 X1 + 0.822 X2. The Fvalue is 761.344 > Ftable 3.10 and the significance value is 0.000 < 0.050. Therefore, H0 is rejected and H3 is accepted.